Yin and Yang of Open Distance Learning: Teacher Trainees’ View - Hafiz, Aidil Hakim Mohd; Rosli, Putera Syahme Nur Iman; Woo, Adelaide; Pek, Lim Seong (Selangor Humaniora Review, 2021)
Open Distance Learning (ODL) is an instructional method where the student and educator are isolated by reality from their physical interactions. Open Distance Learning is beneficial in developing teachers’ language, ICT, and teaching skills. Furthermore, students benefit from ODL by becoming better with their computer and language skills and becoming digitally literate. This study aims to identify the teaching technique used by teacher trainees and the perception of teacher trainees towards ODL. The study applied a survey approach on 44 teacher trainees from three teaching programmes in Universiti Selangor. Findings showed that teacher trainees in UNISEL preferred individual work as their choice of teaching as it was said to be more accessible and had promoted their independent learning ability. In addition, the teacher trainees were mainly neutral to the perceptions of ODL as they were new to this form of teaching approach. The teacher trainees would need more practice exploring the possible strategies for ODL and learning to adapt to students’ needs during practical teaching. To sum up, it is in the hope that this study will aid future teacher trainees in their understanding of ODL teaching and exposure to the new norm and reality of education today.